Determinan Keputusan Pembelian Pada Produk Scarlett Whitening - Vitria, Aida .; Fitriani, Desy; Syahrani, Syahrani; Abdurrahin, Abdurrahim (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
This research aims to determine: The influence of promotions, prices and product variants on purchasing decisions for Scarlett Whitening products among students at the Faculty of Economics, UNISKA MAB, both simultaneously and partially. This research design is quantitative research. The research population was all students from the Faculty of Economics, UNISKA MAB and a sample of 90 respondents. The results of this research show: this test produces information that the three independent variables simultaneously have a significant influence on purchasing decisions for Scarlett Whitening Products. Meanwhile, partial test results show that promotion variables, price and product variants have a significant influence on purchasing decisions for Scarlett Whitening products.